Identification of putative biomarkers for the serodiagnosis of drug-resistant Mycobacterium tuberculosis - Zhang Lu; Wang Qingzhong; Wang Wenjie; Liu Yanyan; Wang Jie; Yue Jun; Xu Ying; Xu Wenxi; Cui ZhenLing; Zhang Xuelian; Wang Honghai (Proteome Science, 2012)
Abstract Background Early diagnosis and treatment of Mycobacterium tuberculosis infection can prevent most deaths resulting from this pathogen; however, multidrug-resistant strains present serious threats to global tuberculosis control and prevention efforts. In this study, we identified antigens that could be used for the serodiagnosis of drug-resistant M. tuberculosis strains, using a proteomics-based analysis. Results Serum from patients infected with drug-resistant or drug-susceptible M. tuberculosis strains and healthy controls was subjected to two-dimensional gel electrophoresis using a western blot approach. This procedure identified nine immunoreactive proteins, which were subjected to MALDI-TOF-MS analysis. Six recombinant proteins, namely rRv2031c, rRv0444c, rRv2145c, rRv3692, rRv0859c, and rRv3040, were expressed and used to determine the immuno-reactivity of 100 serum samples. Antibody reactivity against rRv2031c, rRv3692, and rRv0444c was consistently observed. Among them, the best sensitivity and specificity of rRv3692 were 37% and 95% respectively. Furthermore, when rRv2031c and rRv3692 or rRv2031c, rRv3692, and rRv0444c were combined in 2:1 or equal amounts, the assay sensitivity and specificity were improved to 56.7% and 100% respectively. Conclusions These results suggest that Rv2031c, Rv3692, and Rv0444c are possible candidate biomarkers for effective use in the serodiagnosis of drug-resistant tuberculosis infections, and a combined formula of these antigens should be considered when designing a subunit assay kit.